2014
DOI: 10.1021/jo5001719
|View full text |Cite
|
Sign up to set email alerts
|

From Propargylamides to Oxazole Derivatives: NIS-Mediated Cyclization and Further Oxidation by Dioxygen

Abstract: NIS-mediated iodocyclization of N-sulfonyl propargylamides for the synthesis of various oxazolidines and iodoalkylidenedihydrooxazoles via a 5-exo-dig process is developed. The resulting iodoalkylidenedihydrooxazoles can be further transformed into the corresponding oxazoles in the presence of dioxygen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…Wan team [55] reported the iodine mediated regioselective annulation of N‐sulfonyl propargyl‐amides 72 through 5‐ exo ‐dig intra‐molecular [56] process that afforded a variety of oxazoles 73 . N,N ‐Dimethylformamide (DMF) was used as an optimal solvent, and a broad substrate scope was illustrated (Scheme 28).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wan team [55] reported the iodine mediated regioselective annulation of N‐sulfonyl propargyl‐amides 72 through 5‐ exo ‐dig intra‐molecular [56] process that afforded a variety of oxazoles 73 . N,N ‐Dimethylformamide (DMF) was used as an optimal solvent, and a broad substrate scope was illustrated (Scheme 28).…”
Section: Literature Reviewmentioning
confidence: 99%
“…58 In 2014, Wan and co-workers reported the iodocyclization of N-propargyl-N-sulfonylamides 100 in the presence of NIS as the halogenating agent to give various 5-acyloxazoles 102 (Scheme 24). 59 When the reaction was performed in N,N-dimethylformamide at room temperature, 5-(1-iodoalkylidene)-4,5-dihydrooxazoles 101 were obtained in good yields. The oxidation of 5-(1-iodoalkylidene)-4,5-dihydrooxazoles 101 into 5-acyloxazoles 102 in the presence of molecular oxygen at 80 °C was further investigated.…”
Section: Scheme 21 Synthesis Of 3-iodoquinolinesmentioning
confidence: 99%
“…quantities and can be carried out in a one-pot fashion. 59 In 2015, they reported a high-yielding formal [3+2] annulation of N-propargyl-N-tosylamides 103a (Z = NTs) to access tetrazoles 104 and dihydroimidazoles 105a (Scheme 24). 60 The cyclization occurs via oxygen-atom transfer from the amide moiety to the alkyne with the intermediacy of NIS as a halogenating source and TMSN 3 as coupling partner.…”
Section: Syn Thesismentioning
confidence: 99%
“…18 Recently, Hashmi et al reported an elegant synthesis of halogenated oxazoles via the gold-catalyzed formation of alkylideneoxazolines (path e) 19 followed by the halogenation of them (path f). 18 Such a method have been extended to oxazole synthesis with the introduction of heteroatomic or carbon functional groups 20,21 as well as the further oxidation of iodinated alkylideneoxazolines (path g) 22 by Hashmi's and other groups. However, before our report on λ 3 -iodane-mediated oxidative cycloisomerization, 8 these two-step approaches to various functionalized oxazoles has been known.…”
Section: -Iodane-mediated Cycloisomerization/functionalization Reactionsmentioning
confidence: 99%